2022
DOI: 10.3390/agronomy12092220
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive Application Effects of Washed Rice Water on Plant Growth, Soil Chemical Properties, Nutrient Leaching, and Soil Bacterial Population on Three Different Soil Textures over Three Planting Cycles

Abstract: The benefits of washed rice water (WRW) as a plant fertilizer, particularly over a consecutive application period, are not well studied. An experiment was therefore carried out to determine: the continuous effects of applying unfermented (F0) and 3-day fermented (F3) WRW on the: (1) soil chemical properties, soil bacterial count, and the growth and plant nutrient content of a test crop, choy sum (Brassica chinensis var. parachinensis), grown on three contrasting soil textures (sandy clay loam, clay, and silt l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…No consistent pattern was observed in terms of increasing plant growth, nutrient content, nutrient uptake, or soil nutrient content in the subsequent planting cycles. These observations are in contrast to those reported by [ 19 , 21 ], who observed that the effects of WRW on the growth of choy sum and kangkung had amplified over time. During the first planting cycle, WRW-treated plants experienced lackluster growth that was only slightly or no better than that of the control plants that received only tap water.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No consistent pattern was observed in terms of increasing plant growth, nutrient content, nutrient uptake, or soil nutrient content in the subsequent planting cycles. These observations are in contrast to those reported by [ 19 , 21 ], who observed that the effects of WRW on the growth of choy sum and kangkung had amplified over time. During the first planting cycle, WRW-treated plants experienced lackluster growth that was only slightly or no better than that of the control plants that received only tap water.…”
Section: Discussioncontrasting
confidence: 99%
“…Acknowledging the significance of WRW reuse in agriculture and recognizing the limitations of most existing studies, [ 19 ] recently conducted a comprehensive and scientifically rigorous investigation into WRW's use as a plant fertilizer. They found WRW contained, on average, in mg L −1 : 81 N, 16 NO 3 –N, 18.8 NH 4 –N, 1452 S, 65 P, 131 K, 24 Ca, 25 Mg, 0.18 Cu, 0.07 Zn, and 0.12 B.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global demand for fresh water in 2025 is projected to increase by 55% (Park, 2013). The increase is due to climate change and an increase in world population, which prompted the United Nations to advocate for more effective water management (Paquin and Cosgrove, 2016), where wastewater is used and reused or recycled for other purposes, rather than being thrown away (Nabayi et al, 2022). The utilization of rice washing wastewater can be proven through research.…”
Section: Introductionmentioning
confidence: 99%